Quantum thermodynamics in the interior of a Reissner–Nordström black-hole - Musmarra, Juan Ignacio (2020)
We study the interior of a Reissner–Nordström Black-Hole (RNBH) using Relativistic Quantum Geometry, which was introduced in some previous works. We found discrete energy levels for a scalar field from a polynomial condition for the Heun Confluent functions expanded around the effective causal radius r∗. From the solutions it is obtained that the uncertainty principle is valid for each energy level of space–time, in the form: Enr∗,n=ħ∕2, and the charged mass is discretized and distributed in a finite number of states. The classical RNBH entropy is recovered as the limit case where the number of states is very large, and the RNBH quantum temperature depends on the number of states in the interior of the RNBH. This temperature, depending of the number of states of the RNBH, is related with the Bekenstein–Hawking (BH) temperature: TBH≤TN<2TBH.